The assessment of the relationship between anticholinergic burden and short-term blood pressure variability - Cevdet Furkan Köşker; Reşit Emre Alparğan; Muhammed Ali Coşkuner; Gökhan Köker; Bilgin Bahadır Başgöz (BMC Pharmacology and Toxicology)
Abstract Background This study aimed to investigate the relationship between short-term blood pressure variability (BPV) and anticholinergic burden (ACB) in adults with hypertension. Methods This study included 238 hypertensive patients aged 50 and older who underwent ambulatory blood pressure monitoring. The medications used by the patients were recorded, and the ACB of each medication was calculated using the ACB Scale. The BPV was assessed based on 24-hour ambulatory blood pressure measurements using three methods: standard deviation (SD), coefficient of variation of the standard deviation (SD-CoV), and weighted standard deviation (wSD), with evaluations conducted for both day-time and night-time periods. Results A total of 139 patients (58.40%) had no ACB score, 64 (26.89%) had an ACB score of 1, and 35 (14.71%) had an ACB score of 2 or higher. ACB scores were significantly higher among patients with heart disease, and ACB tended to increase with age. However, no statistically significant relationship was found between ACB and mean blood pressure, nocturnal blood pressure dips, or any parameters of short-term BPV including Sd, SD-CoV and wSD. Conclusion No significant association was found between ACB and short-term BPV. To the best of our knowledge, this is the first study to investigate this relationship, which may inspire further research.